The Use of Direct Method in Teaching Speaking to Grade Eight MTs Negeri 2 Kota Jambi in the Academic Year 2019/2020 - Damairi Damairi; Suyadi Suyadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This article investigates how the teacher use direct method in teaching speaking, how the students encountered speaking, and found out how the students performed their activeness and creativeness on speaking activities by using direct method. This research was classroom action research (CAR) which used research design of the spiral model by Kemmis and Teggart (1988). It consisted of four Phases in one cycle; they are Planning, acting, observation and reflecting. This reserach contained three cycles in which each cycle consisted three meetings. The first of which was to find if any problems and difficulties face by the students and then made some revisions. The second cycle was to implement the revised plan and find out if still any problems. In the teaching and learning hoffully in the third cycle the students and the teacher did not find any difficulties faced the students anymore during the teaching and learning activilties. While we are teaching and learning process followed the steps direct method. They are showing some pictures to students, asking some questions to students. Answering some questions from teacher and asking some questions to their friend or their teacher. The subject of the study is the students of class 8E MTs Negeri 2 Kota Jambi. The data were collected based on the teacher’s note and students’ diaries supported by recording in each meeting on each cycle. The result showed that the teacher used direct method in teaching speaking by following five steps of direct method: showing the pictures, asking questions, answering the questions, asking questions by students and answering their friends‘ questions. The teacher designed some activities, done by students adjusted to the five steps in direct method and the activities made students more active and creative and involved in the learning process. The students also followed all the scenerios of learning process and they were more active and creative during teaching and learning process. However, the students still faced difficulties to make creative answering and questioning. The teacher made some revisions in each cycle. The class atmospieres showed that alive, all of studentts active to speak to ask and aswering questions in their group based on the pictures showed.